Interleukin-2 and dendritic cells as adjuvants for surgical therapy of tumours associated with human papillomavirus type 16 - Bubeník, Jan; Mikysková, Romana; Vonka, Vladimír; Mendoza, Luis; Símová, Jana; Smahel, Michal; Indrová, Marie (Vaccine, 2003)
Moderately immunogenic HPV 16-associated tumours TC-1 (MHC class I(+), HPV 16 E6/E7(+), G12V Ha-ras(+)) and MK16/1/III ABC (MHC class I(-), HPV 16 E6/E7(+), G12V Ha-ras(+)), both of the H-2(b) haplotype and transplanted in syngeneic mice, were used to examine the adjuvant effects of IL-2 and dendritic cells for surgical therapy. Mice were inoculated s.c. with the respective tumour cells, and when the tumours reached 8-12 mm in diameter, they were extirpated. Three days after surgery, the experimental mice were treated with IL-2, IL-2 gene-modified tumour vaccines, or dendritic cells, injected s.c. to the site of previous surgery. It has been found in both, MHC class I(+) and MHC class I(-) tumours that the recombinant IL-2 and IL-2 gene-modified vaccines substantially reduced the tumour recurrence rate and inhibited growth of tumour recurrences. The dendritic cells were significantly effective only in mice with surgical minimal residual TC-1 (MHC class I(+)) tumour disease and when injected before they have reached the terminal stage of their differentiation.
Keywords: Interleukin-2; Papillomaviridae; infekce onkogenními viry; rekombinantní proteiny; myši inbrední C57BL; Cancer Vaccines; mužské pohlaví; Papillomavirus Infections; Mice; Recombinant Proteins; Tumor Cells, Cultured; kombinovaná terapie; interleukin-2; Dendritic Cells; infekce papilomavirem; dendritické buňky; zvířata; Tumor Virus Infections; myši; Combined Modality Therapy; adjuvancia imunologická; Adjuvants, Immunologic; nádorové buňky kultivované; protinádorové vakcíny; Mice, Inbred C57BL; Male; Animals